Motivation and Partner Preferences: Key Drivers of Willingness to Spend Money among Dating App Users - Nisrina Nadhifah; Johan, Irni Rahmayani; Riany, Yulina Eva (Universitas Ahmad Dahlan, 2025)
In the current digital era, the pursuit of romantic relationships has significantly shifted toward online platforms, with dating applications emerging as a prevalent medium. Individuals engage with these apps for a variety of motivations, ranging from entertainment to the pursuit of meaningful connections. Dating apps offer numerous features that allow users to search for partners based on specific personal preferences. Users who are actively seeking partners often demonstrate a willingness to invest financially in the development of these relationships. Distinct from previous studies, this research explicitly explores the relationship between users’ motivations, partner preferences, and their willingness to spend money within the context of dating apps. A total of 1,635 young adults aged 20 to 34 were surveyed through social media platforms, and the data were analyzed using descriptive statistics and structural equation modeling (SEM). The results reveal that motivation significantly influences partner preferences, and both variables—motivation and partner preferences—significantly predict users’ willingness to spend money. These findings contribute to a deeper understanding of behavioral patterns in digital romantic engagement and offer insights into how dating applications may shape financial decision-making in intimate relationships. This study advances the discourse on digital intimacy and consumer behavior by highlighting psychological and relational factors that drive financial investment in online dating contexts. Furthermore, it provides practical implications for individuals seeking to better understand and regulate their motivations and financial behaviors when engaging with dating applications.